Analisis Kepuasan Mahasiswa STMIK Borneo Internasional Balikpapan Pada Website SIMAK Menggunakan PIECES Framework - Nurazizah Amelia M; Jjoy Nashar Utamajaya; Dilla Seltika Canta (STMIK Budi Darma, 2022)
The use of the website in the education sector has been implemented by the STMIK BI Balikpapan campus in the form of the website http://stmik-borneo.ac.id as a forum for information for students, lecturers and the wider community. Website services are certainly supported by many features for information such as student data, academic activities, payments, grades, and even student academic services. SIMAK is an information forum for students to collect student data in the form of academic information, achievements, research and counseling forums with academic supervisors on the STMIK BI Balikpapan campus. The website that is currently in use will of course always require system development according to the needs of its users, especially students. To identify problems, it is necessary to identify problems to find out how satisfied students are on the SIMAK website. One of the evaluation methods is the PIECES method (performance, information, economy, control, efficiency, service). You can determine satisfaction for each domain based on the PIECES method, which consists of performance, information, economy, control, efficiency, and service in measuring student satisfaction for the SIMAK website. Research results from Performance get a value of 4.19, Information get a value of 3.89, Economy gets a value of 3.96, Control gets a value of 4.03, Efficiency gets a value of 4.15 and service gets a value of 4.03. So that the average value obtained is 4.04, it can be categorized as students who feel SATISFIED with the SIMAK website.